The stranger next door : the story of a small community's battle over sex, faith, and civil rights - Stein, Arlene (Beacon Press, 2001)
In a book that combines strong on-the-ground research and lucid analysis with a novelist's imaginative sympathy, Arlene Stein sets out to discover why a small town with no apparent queer population became the site of a bitter battle over gay rights.